Information seeking behavior and challenges in digital libraries - Tella, Adeyinka, 1972-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book addresses the problems of usability and search optimization in digital libraries, with topics addressing all aspects of information seeking activity"--Provided by publisher.
Role of social networking for information seeking in a digital library environment / Ganiyu Ojo Adigun, Oluwole Akanmu Odunola, Adewale Joel Sobalaje -- Barriers to information seeking in the digital libraries / Ajayi Ayo Oluwaseun -- Digital libraries as information superhighway / Prakash Dongardive.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 07/21/2016).
Keywords: Digital libraries; Digital libraries -- Africa; Information behavior; Electronic information resource searching; Information retrieval; Copyright -- Electronic information resources; Bibliometric approach; Cognitive skills; Copyright; Distance learning; Information-seeking models; Social networking; Trade unionists; Usability; Electronic books